Жанубий Оролбўйи ўзбек шевалари лексикасидаги айрим сўзларнинг этимологик талқини (SCIENCE and SOCIETY, 2022)
In the article was analyzed Uzbek, bilingual and five-language explanatory dictionaries in European, Arabic, Persian-Tajik and other Iranian languages learned from the Mongol, Indo-Dravidian languages, reflection of some borrowed words in two- and five-volume ex- planatory dictionaries of Uzbek language to some extent of phonetic, grammatical and lexical-semantic changes in source languages where necessary from an etymological point of view by comparing dictionaries of the old Uzbek literary language compiled at different times.